1961
DOI: 10.1136/jcp.14.6.603
|View full text |Cite
|
Sign up to set email alerts
|

The tongue and oesophagus in iron-deficiency anaemia and the effect of iron therapy

Abstract: University of Sheffield sYNPosis Biopsies of the tongue and oesophagus were performed on 14 patients with uncomplicated iron-deficiency anaemia before and after treatment with iron. Haemoglobin and serum iron estimations were performed at the same time.Nine patients had clinical evidence of atrophic changes in the tongue before therapy was started. Evidence of regeneration appeared within one or two weeks of starting iron therapy. Two patients showed persistent atrophy. Angular stomatitis and koilonychia were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that this type of deficiency affects growth, mental performance, muscle capacity, thermogenesis, and immunity (6)(7)(8). As far as the digestive tract is concerned, irondeficiency anemia is known to be associated with stomatitis and glossitis (9)(10)(11)(12), with reduction of gastric acid secretion (13), abnormal absorption (14), and changes in intestinal permeability (15).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this type of deficiency affects growth, mental performance, muscle capacity, thermogenesis, and immunity (6)(7)(8). As far as the digestive tract is concerned, irondeficiency anemia is known to be associated with stomatitis and glossitis (9)(10)(11)(12), with reduction of gastric acid secretion (13), abnormal absorption (14), and changes in intestinal permeability (15).…”
Section: Introductionmentioning
confidence: 99%
“…This uncommon syndrome of Paterson-Kelly, sometimes named the syndrome of Plummer-Vinson, the syndrome of Waldenstr6m and Kyellberg or sideropenic dysphagia, is mostly seen in middle-aged women from Scandinavian and Anglo-Saxon countries [12]. In 1922 Plummer described this syndrome as "hysterical dysphagia" [1].…”
mentioning
confidence: 99%
“…The activity of certain enzyme systems is altered in iron deficiency (Beutler, 1959;Jacobs, 1961;Dagg et al, 1966). These changes have been suggested as a cause of certain effects, including symptoms (Baird et al, 1961) and in particular fatigue (Beutler el al., 1960).…”
Section: Discussionmentioning
confidence: 99%